Milk Composition and Milk Quality of Saanen Crossbreed Goats Supplemented by Mineral Blocks - M. F. Mohd Noor; N. D. Rusli; K. Mat; C. H. Hasnita; P. Mira (Tropical Animal Science Journal, 2020)
The objective of this study was to investigate the effect of urea molasses multi-nutrient mineral block (UMMB) and medicated urea molasses multi-nutrient mineral block (MUMB) supplemented group on milk composition and milk quality of Saanen lactating does. A 90-day feed trial was conducted at a dairy goat farm in Felda Kemahang, Tanah Merah, Kelantan, Malaysia. Twenty four (24) Saanen lactating does (average milk yield < 1 L/d) were randomly assigned to four groups with six (6) goats each. Animals fed a basal diet, which consisted of 3 kg Napier grass (Pennisetum purpureum) and 1 kg commercial goat pellet as a control group. The experimental groups received equal amounts of basal diet with supplementation of UMMB and MUMB which were formulated using local agriculture by-products; and commercial mineral block (CMB), respectively. Milk samples were collected every two weeks for the analyses of milk composition, i.e., protein, fat, lactose, total solids, density, freezing point, pH, and temperature using EKOmilk analyzer. All results were analyzed using one-way ANOVA followed by Tukey’s test by SPSS software version 23. It was found that milk yield in the group supplemented with UMMB (1.52 L/d) was significantly higher (p<0.05), followed by MUMB (1.31 L/d), CMB (0.96 L/d), and control (0.78 L/d). Besides, the different group did not cause significant effect (p>0.05) on milk composition and total bacteria count. Meanwhile, iron milk content in goat supplemented with MUMB (1.46 mg/g) was significantly lowered (p<0.05), approaching the optimum value (0.36-0.75) compared to the control (4.08 mg/kg). In conclusion, UMMB and MUMB supplements had improved milk quality in terms of iron content and fatty acid concentration, which potentially can be utilized as feed supplements to increase the productivity of lactating goats.